(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2022)
Although ’ Identity ’ in its total and popular sense, has the great ancientness and equality with the human being civilization history, the record of this controversy is not so much precedent. Ease and abstainer of the sense of identity in the process of recognition and perception, bring us amulti-dimensional and complicated phenomenon. Since the city is a window for presentation of community thoughts to the outer world and is the bedrock for creation of civic life, relation of identity and urban landscape become an effective category on correlated sciences with this zone and effort to find out the essence of urban landscape for evaluation of immense intervention politics on current cities is obligatory. This article aims to describe identity and urban definitions by applying the recent theory of ’ Urban Landscape Identity ’ and quantize identity as a qualitative object as well as analyzing different dimensions of thisconcept and finally contribute to its concise literature. Because of the following reasons, the aim of this paper is not to present minute strategies for continuing the identity of urban landscape: First, the urban studies are so vast that it is not possible to present a certain approach for that. Second, prerequisite of detailed approach is presentation of voluminous report, which will be far from the aim of this paper. Third, It’s the first time that this subject is introduced in an academic paper and it’s seemed that basic and extended analyze is more beneficial than minute technique programming.